The 12th International Conference on "Photosynthesis and Hydrogen Energy Research for Sustainability 2024": in honour of John Allen,Eva-Mari Aro, İbrahim Dinçer, Kazunari Domen, Elizabeth Gantt, and Andrey Rubin - M. ZIVCAK; J. KERN; T. TOMO; G. SOYKAN; J.J. EATON-RYE; S.I. ALLAKHVERDIEV; B.D. BRUCE (Photosynthetica, 2025)
The 12th International Conference "Photosynthesis and Hydrogen Energy Research for Sustainability 2024" was organised in honour of John Allen, Eva-Mari Aro, İbrahim Dinçer, Kazunari Domen, Elizabeth Gantt, and Andrey Rubin, by Bahçeşehir University in Istanbul from 13 to 19 October 2024. The International Society of Photosynthesis Research (ISPR) and the International Association for Hydrogen Energy (IAHE) supported the event. In the brief report, we provide a summary of the conference, the scientific contributions of honoured scientists, and a brief content of individual sessions. We specifically focused on the participation of young researchers, their presentations and awards.